(untitled) (Research Nepal Journal of Development Studies, 2021)
Buddhists Economics is economic science based on Buddhists Philosophy specially focused on the noble eightfold path. Ethnography denotes the detailed cultural ethnicity profile of a specified community. Thus it is an ethnicity graph of Tamangs of Temal Rural Municipality from Buddhists’ economic perspective. To get the detailed cultural and economic profile of Tamang of Temal the study has been prepared. It is an ethnography of Tamang of Temal from Buddhist economics and right livelihood. Finally, Tamang is Buddhists but they are highly influenced by different ideologies and now turned into a different type of unique Temal Tamang Buddhists.